Carcinoma of the lung in Ontario gold miners: possible aetiological factors. Issue 12 (December 1991) - Kusiak, R A; Springer, J; Ritchie, A C; Muller, J
Abstract : A cohort of 54, 128 men who worked in Ontario mines was observed for mortality between 1955 and 1986. Most of these men worked in nickel, gold, or uranium mines; a few worked in silver, iron, lead/zinc, or other ore mines. If mortality that occurred after a man had started to mine uranium was excluded, an excess of carcinoma of the lung was found among the 13, 603 Ontario gold miners in the study (standardised mortality ratio (SMR) 129, 95% confidence interval (95% CI) 115-145) and in men who began to mine nickel before 1936 (SMR 141, 95% CI 105-184). The excess mortality from lung cancer in the gold miners was confined to men who began gold mining before 1946. No increase in the mortality from carcinoma of the lung was evident in men who began mining gold after the end of 1945, in men who began mining nickel after 1936, or in men who mined ores other than gold, nickel, and uranium. In the gold mines each year of employment before the end of 1945 was associated with a 6.5% increase in mortality from lung cancer 20 or more years after the miner began working the mines (95% CI 1.6-11.4%); each year of employment before the end of 1945 in mines in which the host rock contained 0.1% arsenic was associated with a 3.1% increase in lung cancer 20 years or more after exposure began (95% CI 1.1-5.1%); and each working level month of exposure to radon decay products was associated with a 1.2% increase in mortality from lung cancer five or more years after exposure began (95% CI 0.02-2.4%). A comparison of two models shows that the excess of lung cancer mortality in Ontario gold miners is associated with exposure to high dust concentrations before 1946, with exposure to arsenic before 1946, and with exposure to radon decay products. No association between the increased incidence of carcinoma of the lung in Ontario gold miners and exposure to mineral fibre could be detected. It is concluded that the excess of carcinoma of the lung in Ontario gold miners is probably due to exposure to arsenic and radon decay products.